Topotactic synthesis of high-entropy sulfide nanosheets as efficient pre-catalysts for water oxidation. Issue 34 (11th April 2023) - Guo, Min; Li, Pengfeng; Wang, Anran; Wang, Jiale; Chen, Jinyue; Lei, Fengcai; Hao, Pin; Sun, Xu; Xie, Junfeng; Tang, Bo
Abstract : Herein, quinary CoFeNiCuCr sulfide nanosheets with a high-entropy feature and rough surface were fabricated via a topotactic transformation pathway, and display facile pre-oxidation and improved intrinsic activity towards the robust oxygen evolution reaction. Abstract : Herein, quinary CoFeNiCuCr sulfide nanosheets with a high-entropy feature and rough surface were fabricated via a topotactic transformation pathway from high-entropy layered metal hydroxides, and display facile pre-oxidation and improved intrinsic activity towards the robust oxygen evolution reaction.